Mutation in the COL2A1 gene is associated with acetabular dysplasia - Xin, Miaomiao; Guan, Xin; Yang, Jiangfei; Li, Yi; Man, Zhentao; Sun, Hongsheng; Fu, Min (Frontiers in Genetics, 2025)
BackgroundDevelopmental dysplasia of the hip (DDH) is one of the most common developmental disorders worldwide, caused by a combination of genetic and environmental factors.MethodsTo investigate the genetic etiology of DDH in a proband (a 27-year-old male), we reviewed the patient’s clinical data and collected peripheral blood samples from the proband and his parents. Genomic DNA was extracted, and polymerase chain reaction (PCR) amplification was performed. Clinical whole-exome sequencing (WES) using next-generation sequencing (NGS) was conducted to identify potential mutation sites, which were then validated through Sanger sequencing. Bioinformatics analysis was performed to assess the pathogenicity of the identified variant, and 3D protein modeling was conducted to predict its impact on protein structure.ResultsThe proband presented with pain in bilateral hips, and based on clinical symptoms, laboratory findings and imaging studies, the final diagnosis was considered to be acetabular dysplasia with overlapping secondary synovial chondromatosis. Family history revealed similar symptoms in the proband’s father, while the grandparents and other family members were unaffected. The patient underwent bilateral total hip arthroplasty and synovectomy. NGS and Sanger sequencing identified a heterozygous missense mutation in the COL2A1 gene (ex13, c.823C > T; p.Arg275Cys) in both the proband and his father, while this mutation was absent in the mother. Bioinformatic analysis indicated that the c.823C > T (p.Arg275Cys) variant is pathogenic, and structural modeling demonstrated that the substitution of arginine with cysteine at residue 275 altered the protein structure.ConclusionOur findings highlight the diagnostic utility of NGS in identifying precise genetic causes of DDH. The identification of the COL2A1 gene mutation in this present case represents a novel clinical phenotype, expanding the spectrum of disorders associated with COL2A1 mutations.